Glaciological Data Collected by the 33rd Japanese Antarctic Research Expedition in 1992 - KAMIYAMA, Kokichi; FURUKAWA, Teruo; MAENO, Hideo; KISHI, Takayuki; KANAO, Masaki (National Institute of Polar Research, 1994)
P(論文) departmental bulletin paper